STATISTICAL ANALYSIS ON FACTORS INFLUENCING ON SHIFT IN CROPPING PATTERNS IN DIFFERENT AGRO-CLIMATIC ZONES OF KARNATAKA - G. R. HALAGUNDEGOWDA; M. S. NAGARAJA; H. K. MEENAKSHI (The Bioscan, 2015)
The study was carried out to assess the factors influencing the shift in cropping pattern in different Agro climatic zones of Karnataka. The study period from 1992 to 2012 was divided into two decades: from 1992-2002 and from 2002-2012. Herfindhal index has been used in this study to measure the extent of Shift in Cropping Pattern. Principal Component Regression (PCR) was used to know the Factors that influence the shift in cropping pattern in both periods. The Result of PCR indicates that PC1 (-0.00027* & 0.000226*) and PC2 (-0.00027* & 0.00054*) were Significant in both the periods (R2was 0.73 & 0.68 for both period of study respectively). The factors such as amount of rainfall (0.490 & 0.574), rural literacy (0.583 & 0.574), Forest area (0.505 & 0.507) were significantly contributing to PC2 in both periods and the number of regulated markets (0.326 &0.365),Small holders (0.353 & 0.371), Net irrigated area (0.325 & 0.344), area under high yielding varieties (0.351 & 0.357) were significantly contributing in PC1 in both periods of study.